2(6a+7)=4(a-1)

Simple and best practice solution for 2(6a+7)=4(a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6a+7)=4(a-1) equation:



2(6a+7)=4(a-1)
We move all terms to the left:
2(6a+7)-(4(a-1))=0
We multiply parentheses
12a-(4(a-1))+14=0
We calculate terms in parentheses: -(4(a-1)), so:
4(a-1)
We multiply parentheses
4a-4
Back to the equation:
-(4a-4)
We get rid of parentheses
12a-4a+4+14=0
We add all the numbers together, and all the variables
8a+18=0
We move all terms containing a to the left, all other terms to the right
8a=-18
a=-18/8
a=-2+1/4

See similar equations:

| (-10)x-1=99 | | -4/9(18x-36)=-88 | | 7+3e=4(2) | | 7t+4t-2=20 | | -2+4(5k+-9)=-96+3k | | 19-y=165 | | 3(4x-2)+8=12x+2 | | 2(4x+1)=13x+1-5x1 | | 6x+4x+6=46 | | -6-5z=-7z | | -5x+5(3x-12)=-150 | | 6(x+5=3(x-14 | | 7d-3=3+6d | | 2w+w+2w+w=60 | | (1/3)x+4=9 | | -7y+1=8y+3 | | 1/6x-(6)=6 | | -14=2x-3(4x-12) | | 41.5+3/6x=60 | | 8x-3=6x8x+7 | | u=10=6u | | -183=5x-3(-6x-8) | | 7y-5y-10=16.02 | | 1/6x-(6)=-6 | | -268=2x+6(3x-18) | | 5(2x-6)=-10x-30 | | -5-(4x)=3 | | v=2v-2 | | -7x+2=33 | | 2x+x+3+x=183 | | 7h=3 | | 8(30+-1y)+12y=268 |

Equations solver categories